PREVALENCE OF THYROID MICROSOMAL AND THYROGLOBULIN AUTOANTIBODIES IN GOITROUS LESIONS - Tayyab, Muhammad; Bhatt, Khal1l-Ur- Rehman; Ditta, Allah (Journal of Ayub Medical College Abbottabad, 2001)
background: this prospective study was done to evaluate the serum levels of microsomal and thyroglobulin autoantibodies in patients with toxic diffuse goiter and nodular goitre (non-toxic) undergoing radio-iodine therapy and thyroidectomy respectively. methods: forty-eight patients suffering from thyroid disorders. 29 with nodular goiter and 19 with toxic diffuse goitre (TDG) and 15 age & sex-matched normal controls were studied. thyroid microsomal (MSAB) and thyroglobulin autoantibodies (TGAB) were estimated in the sera of all the subjects using the commercially available kits based on tanned red cell haemagglutination technique. results: MSAB seropositivity in TDG and nodular goitre was found to be 78.9% and 51.7% respectively. on the other hand, TGAB seropositivity was 57.9% and 27.6% in cases of TDG and nodular goitre. 13.3% and 6.7% of the normal controls were positive for MSAB and TGAB respectively. Conclusion: These findings indicate that autoimmunity is thyroid disorders implicated in the genesis of commonly occurring